1978
DOI: 10.1016/0035-9203(78)90167-0
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of the sporogonic development of Plasmodium falciparum in Anopheles gambiae

Abstract: This paper describes the fine structure of the sporogonic development of Plasmodium falciparum in its natural vector Anopheles gambiae (Species A) as seen by scanning and transmission electron microscopy. The parasite was derived from naturally infected volunteers and the vector maintained under natural conditions at the MRC Laboratories, Fajara, The Gambia. Sporogonic development of P. falciparum is similar to that described for other Plasmodium spp. There are however greater similarities between P. falciparu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 30 publications
5
70
1
Order By: Relevance
“…Partitioning of the spindle pole plaque has also been observed by electron microscopy. A band of striated fibers termed the couche fibrillaire spans the separating plaques (42,140,161). This structure may represent centrin fibers, since similar structures are observed in algae and yeast (89,164,192).…”
Section: Role In Apicomplexan Replicationmentioning
confidence: 86%
See 1 more Smart Citation
“…Partitioning of the spindle pole plaque has also been observed by electron microscopy. A band of striated fibers termed the couche fibrillaire spans the separating plaques (42,140,161). This structure may represent centrin fibers, since similar structures are observed in algae and yeast (89,164,192).…”
Section: Role In Apicomplexan Replicationmentioning
confidence: 86%
“…Nuclear division proceeds without nuclear membrane breakdown (12,26,59,79,130,161). Spindle microtubules are nucleated from electron-dense, amorphous plaques associated with nuclear invaginations and embedded in the nuclear membrane (12,26,82,109,140,146,157).…”
Section: Microtubules In the Apicomplexa Organizationmentioning
confidence: 99%
“…Gametocytes had a surrounding erythrocyte membrane, whereas crosssections of ookinetes did not. 41,[49][50][51][52][53][54][55] Examination of erythrocyte-free elongated parasites showed definitive ookinete ultrastructure, including the apical complex and a pellicle, which was not observed in gametocytes ( Figure 5 ). The apical complex consists of an apical polar ring and micronemes.…”
Section: Ultrastructural Analysis Of P Falciparum Sexual Stage Parasmentioning
confidence: 99%
“…NF54 is one of the 13 initial Nijmegen Falciparum (NF) isolates derived from a Dutch patient. [52][53][54] This strain was maintained in continuous asexual culture according to standard protocol 26 with the exception that no antibiotics were used in the complete medium: RPMI 1,640, 25 mM Hepes, 2 mM l-glutamine, 2.4 g/L NaHCO3, 50 mg/L hypoxanthine, and 10% heat-inactivated AB+ human serum (Interstate Blood Bank, Memphis, TN). Asynchronous asexual stage cultures at 8-15% parasitemia were used to start gametocyte cultures.…”
Section: Ultrastructural Analysis Of P Falciparum Sexual Stage Parasmentioning
confidence: 99%
“…stephensi mosquitoes (Meis et al 1992b), confirming previous results observed with P. falciparum in naturally infected An. gambiae (Sinden & Strong 1978). Recent reports described an enhancement of oocyst development in vitro for P. berghei (Syaffruddin et al 1992), P. gallinaceum and P. falciparum (Warburg & Schneider, 1993), when insect cell lines were added into the culture medium.…”
Section: Oocyst Developmentmentioning
confidence: 99%